A novel type of protein kinase phosphorylates actin in the actin-fragmin complex. - Eichinger, L (1996)
Actin-fragmin kinase (AFK) from Physarum polycephalum specifically phosphorylates actin in the EGTA-resistant 1:1 actin-fragmin complex. The cDNA deduced amino acid sequence reveals two major domains of approximately 35 kDa each that are separated by a hinge-like proline/serine-rich segment of 50 residues. Whereas the N-terminal domain does not show any significant similarity to protein sequences from databases, there are six complete kelch repeats in the protein that comprise almost the entire C-terminal half of the molecule. To prove the intrinsic phosphorylation activity of AFK, full-length or partial cDNA fragments were expressed both in a reticulocyte lysate and in Escherichia coli. In both expression systems, we obtained specific actin phosphorylation and located the catalytic domain in the N-terminal half. Interestingly, this region did not contain any of the known protein kinase consensus sequences. The only known sequence motif present that could have been involved in nucleotide binding was a nearly perfect phosphate binding loop (P-loop). However, introduction of two different point mutations into this putative P-loop sequence did not alter the catalytic activity of the kinase, which indicates an as yet unknown mechanism for phosphate transfer. Our data suggest that AFK belongs to a new class of protein kinases and that this actin phosphorylation might be the first example of a widely distributed novel type of regulation of the actin cytoskeleton in non-muscle cells.